PENGARUH E-COMMERCE TERHADAP PENJUALAN DAN PEMBELIAN BARANG SECARA ONLINE PADA TOKO NOTEBOOK JAKARTA - Henny Destiana (LPPM Universitas Bina Sarana Informatika, 2010)
Today world trade is no longer limited by space and time. High mobility of people who claim the sales world is able to provide services and goods with instant according to the demand pembeli.Untuk resolve the issue then emerges transactions using the Internet media to connect between sellers and buyers. Transactions via the Internet is better known as E-Commerce, so the presence of E-commerce can improve efficiency and effectiveness in the sales and purchases by utilizing information technology, the price is cheap considering creating a site on the internet cheaper than opening retail outlets in various places , as well as the purchase memalui internet service will be followed by delivery of goods to the buyer Kata Kunci: Ecommerce, Sistem Informasi, Internet